Recent advances in understanding breast cancer and emerging therapies with a focus on luminal and triple-negative breast cancer - El Hachem, Georges (F1000Res, 2019)
Breast cancer is a global health issue. For decades, breast cancer was classified into many histological subtypes on the basis of microscopic and immunohistochemical evaluation. The discovery of many key genomic driver events involved in breast cancer carcinogenesis resulted in a better understanding of the tumor biology, the disease heterogeneity and the prognosis leading to the discovery of new modalities of targeted therapies and opening horizons toward a more personalized medicine. In recent years, many therapeutic options emerged in the field of metastatic breast carcinoma, especially for the luminal subtypes. They were able to transform the course of the disease while maintaining quality of life. However, the options are still limited for triple-negative breast cancer, but the better knowledge of its complex biology and the discovery of molecular targets are promising for more efficient novel therapies.